Mutation of barley HvPDIL5-1 improves resistance to yellow mosaic virus disease without growth or yield penalties - Cheng, Chunyuan; Kan, Jinhong; Li, Shanshan; Jiang, Congcong; He, Xiaoyan; Shen, Huiquan; Xu, Rugen; Li, Boqun; Feng, Zongyun; Yang, Ping (Frontiers in Plant Science, 2022)
The soil-borne yellow mosaic virus disease, which is caused by the bymoviruses barley yellow mosaic virus (BaYMV) and/or barley mild mosaic virus (BaMMV), seriously threatens winter barley production in Europe and East Asia. Both viruses are transmitted by the soil-borne plasmodiophorid Polymyxa graminis and are difficult to eliminate through chemical or physical measures in the field, making breeding for resistant cultivars the optimal strategy for disease control. The resistance locus rym1/11 was cloned encoding the host factor gene Protein Disulfide Isomerase Like 5-1 (PDIL5-1), whose loss-of-function variants confer broad-spectrum resistance to multiple strains of BaMMV/BaYMV. Most resistance-conferring variants have been identified in six-rowed barley landraces/historic cultivars, and their introgression into modern two-rowed malting cultivars is difficult because PDIL5-1 is located in a peri-centromeric region with suppressed recombination. In this study, we used CRISPR/Cas9 genome editing to modify PDIL5-1 in the BaYMV/BaMMV-susceptible elite malting barley cv. ‘Golden Promise’ and obtained the mutants pdil5-1-a and pdil5-1-b. PDIL5-1 in the pdil5-1-a mutant encodes a protein lacking a cysteine residue, and pdil5-1-b contains a protein-coding frameshift. Both mutants were completely resistant to BaYMV. The knockout mutant pdil5-1-b showed complete BaMMV resistance, while pdil5-1-a showed decreased viral accumulation but no disease symptoms if compared to ‘Golden Promise’. Both PDIL5-1 edited lines, as well as the previously produced EMS-induced pdil5-1 mutant ‘10253-1-5’ in the elite malting barley cv. ‘Barke’ background, displayed no growth or yield penalties in garden experiments or bymovirus-free field trials. Line ‘10253-1-5’ showed improved resistance and yield performance compared to the wild-type and its sibling line when grown in infectious fields. Therefore, genome editing of the host factor gene PDIL5-1 could facilitate the breeding of barley varieties with resistance to bymoviruses.